SEDIMETOLOGICAL STUDY OF THE CARBONIFEROUS LOWER IN AIT TAMLIL BOUTONNIERE - Es-Sadiq, Rachid; Algouti, Ahmed; Essemani, Mohamed (European Scientific Journal, ESJ, 2014)
The basin of the lower Carboniferous of Aït Tamlil is located in the western extremity of the Moroccan Central High Atlas (districtof Azilal) (Figure 1). We present in this study the sedimentary evolution of the lower Carboniferous of Aït Tamlil inlier (Central High Atlas), through a multidisciplinary study that involves petrographic, lithostratigraphic and sedimentary environment analysis of the basin deposits (slope deposits, fluvial deposits, fan turbidites). The study revealed that intrinsic factors to the system (lithology of the basin) and extrinsic (tectonic) share the control of this evolution according to the weight of each factor spreading of the platform towards the center of the basin. This basin is formed by four large upper Visean formations and constituted mostly of East-West oriented autochthonous and allochthonous Paleozoic series, as well as siliciclastic and carbonate sedimentary deposits. These formations are distributed as follows: Jbel Imgant, Tizi n’Toutfi, Jbel Abberonech and Iguer complex n’Igherm. Normal sedimentation is continuous in the Aït Tamlil basin and had lasted for deposition phases of jbel Imgant turbidite series and its equivalent platform of Jbel Abberonech, chaotic series of Tizi n’Tnoutfi and that of Iguer n’Igherm can take place on a very short time. The interpretation of these sediments intervenes in the paleogeographic reconstruction of the region.